Association Between the Catechol-O-Methyltransferase (COMT) Val158Met Polymorphism and Manual Performance Asymmetries. Issue 3 (June 2019) - Nogueira, Nathálya G. H. M.; Fernandes, Lidiane A.; Ferreira, Bárbara P.; Batista, Marco T. S.; Alves, Karen C. R.; Parma, Juliana O.
Within the cognitive domain, neuroscience and cognitive psychology researchers have investigated the relationship between handedness and cognitive skills. However, there have been few studies of the three-way association between manual asymmetry, its genetic components, and cognition even though this line of research could further an understanding of asymmetry. One enzyme involved in cognitive functions related to the dopaminergic system and to the prefrontal cortex is the catechol-O-methyltransferase (COMT), and it has a trimodal activity distribution in the human population due to its functional polymorphism known as Val158Met. This study investigated whether this COMT polymorphism is associated with asymmetries in the performance of a manual dexterity task. Forty-two right-handed undergraduate students ( M age = 25.12, SD = 5.84; 15 women, 27 men) performed two trials each of place and remove conditions of the Grooved Pegboard Test with each hand (right and left), counterbalancing the order of the initial or starting hand. We calculated the mean time to perform the task for both hands on both trials and found, as hypothesized, that the Met/Met group gave a more asymmetrical performance than the Val/Met group under the place condition because dopamine levels reduced flexible behavior for the Val/Met group. We suspect that the place condition requires greater interhemispheric connectivity, as it requires a greater cognitive flexibility, and highly asymmetrical individuals are said to be less flexible. The findings of this study suggest a significant association between the COMT polymorphism and manual asymmetry in healthy populations.